Ethical issues in empirical studies of software engineering. - Singer, J.
The popularity of empirical methods in software engineering research is on the rise. Surveys, experiments, metrics, case studies, and field studies are examples of empirical methods used to investigate both software engineering processes and products. The increased application of empirical methods has also brought about an increase in discussions about adapting these methods to the peculiarities of software engineering. In contrast, the ethical issues raised by empirical methods have received little, if any, attention in the software engineering literature. This article is intended to introduce the ethical issues raised by empirical research to the software engineering research community and to stimulate discussion of how best to deal with these ethical issues. Through a review of the ethical codes of several fields that commonly employ humans and artifacts as research subjects, we have identified major ethical issues relevant to empirical studies of software engineering. These issues are illustrated with real empirical studies of software engineering.
Keywords: Empirical studies; Ethical issues; Legal issues; Software engineering; Software engineering processes; Software engineering products